Energy policy and politics in China. - Hood, M. (IEEE spectrum)
In this paper the authors describe how, although sensitive to pollution's threat, China's political leaders have little room for manoeuvre and see worry about greenhouse gases as an ill-affordable luxury in terms of coal-fired electricity generation